Allogeneic Hematopoietic Stem Cell Transplantation in Solid Organ Transplant Recipients: A Retrospective, Multicenter Study of the EBMT. Issue 3 (3rd February 2015) - Basak, G. W.; Wiktor‐Jedrzejczak, W.; Labopin, M.; Schoemans, H.; Ljungman, P.; Kobbe, G.; Beguin, Y.; Lang, P.; Koenecke, C.; Sykora, K. W.; te Boome, L.; van Biezen, A.; et al.
<x xml:space="preserve">Abstract</x> We conducted a questionnaire survey of the 565 European Society for Blood and Marrow Transplantation centers to analyze the outcome of allogeneic hematopoietic stem cell transplantation (alloSCT) in recipients of solid organ transplantation (SOT). We investigated 28 patients with malignant (N = 22) or nonmalignant diseases (N = 6), who underwent 31 alloSCT procedures: 12 after kidney, 13 after liver and 3 after heart transplantation. The incidence of solid organ graft failure at 60 months after first alloSCT was 33% (95% confidence interval [CI], 16–51%) for all patients, 15% (95% CI, 2–40%) for liver recipients and 50% (95% CI, 19–75%) for kidney recipients (p = 0.06). The relapse rate after alloSCT (22%) was low following transplantation for malignant disorders, despite advanced stages of malignancy. Overall survival at 60 months after first alloSCT was 40% (95% CI, 19–60%) for all patients, 51% (95% CI, 16–86%) for liver recipients and 42% (95% CI, 14–70%) for kidney recipients (p = 0.39). In summary, we show that selected SOT recipients suffering from hematologic disorders may benefit from alloSCT and experience enhanced long‐term survival without loss of organ function.